Evaluation of Antifungal Effect of Silver Nanoparticles Against Microsporum canis, Trichophyton mentagrophytes and Microsporum gypseum - Ayatollahi Mousavi, Seyyed Amin (National Institute of Genetic Engineering and Biotechnology, 2015)

(untitled) (Iran J Biotechnol)
BACKGROUND: Dermatophytosis is the common cutaneous infections in humans and animals, which is caused by the keratinophylic fungus called dermatophytes. In recent years, drugs resistance in pathogenic fungi, including dermatophyte strains to the current antifungals have been increased. OBJECTIVES: The aim of this study was to evaluate the antifungal efficacy of AgNPs against Microsporum canis, Trichophyton mentagrophytes , and Microsporum gypseum. MATERIALS AND METHODS: The antifungal susceptibility of nanosilver particles compared with griseofulvin (GR). Its efficacy was investigated against three strains of dermatophytes by both agar dilution and broth microdilution test (BMD). RESULTS: The average minimum inhibitory concentration (MIC) AgNPs on M. canis, T. mentagrophytes and M. gypseum were 200, 180 and 170 μg.mL(-1), respectively. Whereas these strains showed MIC of 25, 100 and 50 μg.mL(-1) for GR. CONCLUSIONS: Our finding indicated that the AgNPs was less active than GR but it had anti-dermatophytic effect.